Thermokinetics of alkyl methylpyrrolidinium NTf2 ionic liquids: Effect of alkyl chain on thermal stability - Quraishi, K.S. (Springer Netherlands, 2017)
Abstract: The thermal degradation of two ionic liquids (ILs) was investigated using thermogravimetric analysis (TG) to establish a relationship between the thermokinetics and thermal stability. N-butyl, N-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide BMPyrroNTf2 and N-octyl, N-methylpyrrolidinium bis(trifluoromethylsulfonyl)imideOMPyrroNTf2 were subjected to thermogravimetric analysis at varying heating rates of 5, 10 and 20 °C min−1 in the temperature range of 50–600 °C. The data obtained were analysed for thermokinetics using Ozawa, Kissinger and Starink methods using differential thermogravimetric (DTG) techniques, and Flynn–Wall–Ozawa (FWO), Kissinger–Akahira–Sunose (KAS) and Starink methods using TG techniques. The results produced very high regression coefficients (R2) values around 0.996, which exhibited that they were best fitted by the kinetics equations. The average calculated activation energy (Ea) of BMPyrroNTf2 using FWO, KAS and Starink methods was 128.6, 123.6 and 124 kJ mol−1, respectively, and 113.7, 107.8 and 108.2 kJ mol−1, respectively, for OMPyrroNTf2 using same empirical methods. This emphasizes that the activation energy is strongly related to the length of the side alkyl chain of a given IL. In other words, the longer the side alkyl chain, the lower the activation energy. The Ea trends with degree of conversion (α) suggest that a single mechanism without formation of intermediates or short-life intermediates was followed by the pyrolysis kinetics. This study introduced thermokinetics as a tool to study the thermal stability of ionic liquids. Graphical Abstract: Figure not available: see fulltext.. © 2017, Akadémiai Kiadó, Budapest, Hungary.